RELIGIOUS MODERATION PRACTICES AS OF INCLUSIVE EDUCATION FOR LOCAL SOCIETY IN LOMBOK (SANGKÃ©P: Jurnal Kajian Sosial Keagamaan, 2022)
The issue of religious moderation in Indonesia has become a trending topic since it was first initiated by the Ministry of Religion of the Republic of Indonesia. This issue does not focus only on socio-religious issues, but also in the economic, political, cultural and educational fields. The concept of religious moderation as inclusive education is important to be applied in the life of religious, cultural, and ethnic diversity in realizing religious harmony. This study analyzes the practice of religious moderation as inclusive education for local communities in Gangga District, North Lombok Regency. The results of this study indicate that the practice of religious moderation between Islam and Buddhism is through tradition Mulik Kaya strengthening unity and oneness among different religious fraternities, reviving local traditions, creating tolerance in diversity, and maintaining harmony betweenMuslim and Buddhist communities. Implement local wisdom values through religious moderation by implementing inclusive education to realize the values of peace and inter-religious harmony in Indonesia.